Curated Collections for Educators: Eight Key Papers about Feedback in Medical Education - Natesan, Sreeja M (Cureus, 2019)
Feedback is an essential part of learning, growth, and academic success. Junior faculty members are often unfamiliar with the grounding literature that defines feedback. Many times they receive little education on providing and receiving feedback, resulting in unhelpful “feedback” for both learners and program leadership alike. This article aims to summarize eight key papers on feedback, to outline relevant information for emerging clinician educators, and identify ways to use these resources for the faculty development.  In order to generate a list of key papers that describes the importance and significance of feedback, the authors conducted a consensus-building process to identify the top papers. In August and September, 2018, the 2018-2019 Academic Life in Emergency Medicine (ALiEM) Faculty Incubator program discussed the topic of feedback in medical education. A number of papers on the topic was highlighted. This list of papers was further augmented using the suggestions and expertise of guest experts who are leaders in the field of medical education and feedback. The authors also used social media to conduct an open call on Twitter for important papers regarding feedback (utilizing #meded, #Feedback hashtags). Via this process, a list of 88 key papers was identified on the topic of feedback in medical education. After compiling these papers, the authorship group engaged in a modified Delphi approach to build consensus on the top eight papers on feedback. These papers were deemed essential by the authors and have been summarized with respect to their relevance to junior faculty members and to faculty developers. In this manuscript, we present eight key papers addressing feedback in medical education with discussions and applications for junior faculty members and faculty developers. This list of articles that can serve to help junior clinician educators grow in their ability to give effective feedback and also serve as resources upon which senior faculty can design the faculty development sessions.